Smoldering myeloma presenting as progressive multifocal leukoencephalopathy: a case report - Troppmann, Martina (BioMed Central, 2012)
INTRODUCTION: Progressive multifocal leukoencephalopathy is an opportunistic infection occurring in patients with severe cellular immunodeficiency. This case highlights the role of cellular immunodeficiency in the reactivation of John Cunningham virus in a case of an early stage plasmacytoma. CASE PRESENTATION: A 76-year-old Caucasian woman presented with progressive left-sided hemiparesis, accompanied by hypoesthesia, hypoalgesia and neuropsychological symptoms. Magnetic resonance imaging demonstrated new hyperattenuating lesions in the right thalamus and left-sided subcortically. A polymerase chain reaction test revealed 4500 copies of John Cunningham virus-deoxyribonucleic acid/ml in cerebrospinal fluid. Human immunodeficiency virus infection was ruled out. A bone marrow biopsy showed an early stage immunoglobulin G-kappa plasmacytoma. Cidofovir (5mg/kg) weekly for three weeks was started. A significant improvement of her neuropsychological symptoms was achieved, but motor system and sensory symptoms did not change. CONCLUSIONS: This case shows a rapid course of progressive multifocal leukoencephalopathy with severe residual deficits. In the diagnostic workup of all patients with atypical neurologic symptoms or immunodeficiency, progressive multifocal leukoencephalopathy should be included as a differential diagnosis.